First report of burrowing parrot (cyanoliseus patagonus) nesting in tree cavities - López, Fernando Gabriel (2018)
The Burrowing Parrot Cyanoliseus patagonus is known to breed in burrows mostly on cliffs and ravines in arid or semi‐arid regions of Argentina and Chile. However, during a tree cavity monitoring project we confirmed at least two active nests in tree cavities. Cavity entrances were located between 3.1 and 5.3 m above the ground in live caldén (Prosopis caldenia) trees, Parque Luro, province of La Pampa, Argentina. One nest failed while the other one successfully produced three fledglings. The absence of cliffs and scarcity of ravines in the region, and the presence of a nesting colony of the Blue‐crowned Parakeet (Thectocercus acuticaudatus) in the site may have promoted the adop‐ tion of this new nesting substrate for the species.